Comorbid depressive symptoms can aggravate the functional changes of the pain matrix in patients with chronic back pain: A resting-state fMRI study - Zhang, Guangfang; Ma, Junqin; Lu, Weirong; Zhan, Hongrui; Zhang, Xuefei; Wang, Kangling; Hu, Yingxuan; Wang, Xianglong; Peng, Weiwei; Yue, Shouwei; Cai, Qingxiang; Liang, Wen; et al. (Frontiers in Aging Neuroscience, 2022)
Objective: The purposes of this study are to explore (1) Whether comorbid depressive symptoms in patients with chronic back pain affect the pain matrix. And (2) Whether the interaction of depression and chronic back pain exacerbates impaired brain function. Methods: Thirty-two patients with chronic back pain without comorbid depressive symptoms and thirty patients with chronic back pain with comorbid depressive symptoms were recruited. All subjects underwent functional magnetic resonance imaging scans. The graph theory analysis, mediation analysis, and functional connectivity analysis were included in this study. All subjects received the detection of clinical depressive symptoms and pain-related manifestations. Result: Compared with the chronic back pain (CBP) group, subjects in the chronic back pain with comorbid depressive symptoms (CBP-D) group had significantly increased functional connectivity in the left medial prefrontal cortex and several parietal cortical regions. The results of the graph theory analyses showed that the area under the curve of small-world property (t = -2.175, p = 0.034), gamma (t = -2.332, p = 0.023), and local efficiency (t = -2.461, p = 0.017) in the CBP-D group were significantly lower. The nodal efficiency in the ventral posterior insula (t = -3.581, p = 0.0007), and the network efficiency values (t = -2.758, p = 0.008) in the pain matrix were significantly lower in the CBP-D group. Both the topological properties and the functional connectivity values of these brain regions were significantly correlated with self-rating depression scale (SDS) scores (all FDR corrected) but not with pain intensity. Further mediation analyses demonstrated that pain intensity had a mediating effect on the relationship between SDS scores and Pain Disability Index scores. Likewise, the SDS scores mediated the relationship between pain intensity and PDI scores. Conclusion: Our study found that comorbid depressive symptoms can aggravate the impairment of pain matrix function of chronic back pain, but this impairment can not directly lead to the increase of pain intensity, which may be because some brain regions of the pain matrix are the common neural basis of depression and chronic back pain.